Awareness among Medical Students about Forensic Odontology - S.M.Krishna Sagar1 , Divya Reddy Pannala2 , Rithya Kuppam3 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Every tooth possesses a set of unique characteristics and the way the teeth are arranged in different oral cavitiesare unique in every individual. Therefore, dentition is useful for individual identification and comparison,especially in mass disasters where the bodies of the victims become mutilated beyond recognition. Forensicodontology deals with the science of dentistry to aid in the administration of justice. There is a huge void inthe number of forensic odontology experts required to meet the demand and those that are actually gettingtrained in this concern. In order to ease this, there is a need to incorporate MBBS undergraduate curriculumwith the shortlisted particulars of forensic dentistry. The study was conducted to evaluate the awareness andknowledge about forensic dentistry amongst the 2nd Year MBBS under graduates in Mahavir Institute ofMedical Sciences. The study showed that the level of awareness on topic was adequate in the participantsbut they had little knowledge about the practical application of forensic odontology in routine practice.Conducting regular seminars and workshops can be helpful to develop the practical skill required in handlingforensic odontology related cases in emergency department.